Peran Masyarakat sebagai Komunikator Pembangunan Peduli Lingkungan - Nuraflah, Cut Alma (Universitas Medan Area, 2019)
The purpose of this study is to describe the role of community as a development communicator of environment care. This research uses a qualitative approach, located in Tanjung Gusta Village, Medan Helvetia District, Medan.The informant in this study was the chairman of Badan Keswadayaan Masyarakat (BKM) of Tanjung Gusta Village, Medan Helvetia. Data collection techniques through interviews, observation and documentation. Data analysis techniques using the model of Miles and Huberman. The results showed that with the buttom up approach, the role of the community in the development process can be maximized, seeing some of the advantages of development communicators from the local community more than communicators from outside the local community,then one of the most effective ways to build awareness of environmental care is to maximize the role of local communities as communicators of development. However, some obstacles found in the process of conveying messages of environmental care development, communication barriers and social barriers (social categories, social exchange and social relations)